Europäische Verschuldung- und Wirtschaftskrise 2008- 2012: die Analyse der Krisenmassnahmen aus der Sicht von den Beteiligten. Zusammenfassung:Eurotsooni majandus- ja finantskriisi lahendusmeetmed ja valikud mõjugruppide seisukohast - Veebel, Viljar; Teder, Allan; Kulu, Liina; Viikmaa, Karmen; Hurt, Ulrika (Estonian Discussions on Economic Policy, 2013)
The European financial crisis in recent years (2008–2012) and economic challenges in long-term perspective, have initiated intensive debates among politicians, academic circles and media. The intensity of the debate has been related to the amplitude of the crisis and to the possible interests, influence and costs of the social stakeholders. The aim of this research is to analyze the interests of crisis management and policy actions from the perspective of social stakeholders (political actors, economic actors, voters and supranational institutions such as European Central Bank). Process tracking and narrative analysis will be used as methodological approaches. The research will first focus on the challenges and dilemmas of the European financial crisis and interests of social stakeholders. The second part of the research will analyze how the social stakeholders managed to influence the policy decisions related to the Eurozone crisis management, which measures were taken and why supranational institutions have been most successful in decision making process.